Common Public Life Values: A Roadmap to Inclusivity and Understanding – the Case of Lebanon - Daou, Ana-Maria (International journal of Asian christianity, 2022)
In the recent past, many religious and secular organisations worked on developing declarations that called for the celebration of all forms of diversity, the protection of Freedom of Religion or Belief, the inclusion of marginalised groups in decision-making, and the promotion of active citizenship. However, the rise of populist movements worldwide increased the propagation of hate speech and violent narratives. This article explores how common public life values in Christianity and Islam could contribute to the development of peaceful and inclusive societies and studies the added layer this provides to practical interfaith dialogue. The article draws on real-life examples from the Lebanese context – especially from the experiences of members of the Forum for Religious Social Responsibility at Adyan Foundation.